IMPLIKASI KEBIJAKAN PENGELOLAAN SUMBER DAYA ALAM TERHADAP ASPEK KEBERLANJUTAN SOSIAL DAN LINGKUNGAN - Illyas Anshori; Aji Setyawan; Aulia Firdaus (JOURNAL OF LAW AND NATION, 2023)
Policy is a critical role of natural resource management (SDA) in Indonesia in maintaining sustainability and balance between economic growth, social welfare and environmental conservation. Indonesia, as a country rich in natural diversity, faces serious challenges in designing adequate natural resource management policies in the contemporary era. Rapid economic growth and urbanization have increased pressure on natural resources, giving rise to conflicts between economic, social and environmental interests. This research aims to explore the implications of natural resource management policies in Indonesia on social and environmental aspects. From a social and environmental perspective, this research highlights the rights of local communities, especially indigenous groups, in the use of natural resources, as well as the importance of their participation in decision making which has implications for environmental sustainability. The research method used is a normative juridical method, by examining library materials and secondary data to analyze normative and legal aspects in natural resource management problems. This research aims to contribute to a deeper understanding of the influence of natural resource management policies on social and environmental aspects in Indonesia, as well as providing a basis for developing more effective and sustainable policies in the future.